Analisis Penggunaan Instagram dan Fintech Crowdfunding Terhadap Minat Membayar Zakat dengan Transparansi Badan Amil Zakat Sebagai Variabel Intervening - Widyar VR; MH Ainulyaqin; Y Ahmad; S Edy (Economic Reviews Journal, 2024)
This research aims to determine the effect of the use of instagram and fintech crowdfunding on interest in paying zakat and to determine the effect of transparency of the amil zakat agency as an intervene variabel between the use of Instagram and fintech crowdfunding on interest in paying zakat in the people of Bekasi Regency. The type of research used is quantitative research, namely by using primary data in the form of a questionnaire. The sampling used is nonprobability sampling with a purposive sampling method. The sample of this research was 100 people from Bekasi Regency using the slovin formula. The data analysis method used the SEM (Structural Equation Model) analysis technique with the PLS (Partial Least Square) method and hypothesis testing was carried out by calculating bootstrapping in structural research. The results of this study prove that all studies support the formulated hypothesis, in which researchers find that the variable use of Instagram, fintech crowdfunding, and transparency of amil zakat agencies directly have a positive influence in influencing people's interest in paying zakat and the transparency of amil zakat agencies as intervening variables can mediate effectively the positive relationship between Instagram and fintech crowdfunding on interest in paying zakat. But only the direct fintech crowdfunding variable and the transparency variable of the amil zakat agency as a mediating variable between fintech crowdfunding and interest in paying zakat have a positive but not significant effect.